Aerobic exercise reduces hippocampal ERK and p38 activation and improves memory of middle‐aged rats. Issue 8 (1st June 2017) - Cardoso, Fabrízio dos Santos; França, Erivelton Fernandes; Serra, Fernando Tadeu; Victorino, Angélica Begatti; de Almeida, Alexandre Aparecido; Fernandes, Jansen; Cabral, Francisco Romero; Venancio, Daniel Paulino; Arida, Ricardo Mario; Gomes da Silva, Sérgio
Abstract: Aging is often accompanied by cognitive decline, memory impairment, and an increased susceptibility to neurodegenerative disorders. Although the physiological processes of aging are not fully understood, these age‐related changes have been interpreted by means of various cellular and molecular theories. Among these theories, alterations in the intracellular signaling pathways associated with cell growth, proliferation, and survival have been highlighted. Based on these observations and on recent evidence showing the beneficial effects of exercise on cognitive function in the elderly, we investigated the cell signaling pathways in the hippocampal formation of middle‐aged rats (18 months old) submitted to treadmill exercise over 10 days. To do this, we evaluated the hippocampal activation of intracellular signaling proteins linked to cell growth, proliferation, and survival, such as Akt, mTOR, p70S6K, ERK, CREB, and p38. We also explored the cognitive performance (inhibitory avoidance) of middle‐aged rats. It was found that physical exercise reduces ERK and p38 activation in the hippocampal formation of aged rats, when compared to the control group. The hippocampal activation and expression of Akt, mTOR, p70S6K, and CREB were not statistically different between the groups. It was also observed that aged rats from the exercise group exhibited better cognitive performance in the inhibitory avoidance task (aversive memory) than aged rats from the control group. Our results indicate that physical exercise reduces intracellular signaling pathways linked to inflammation and cell death (i.e., ERK and p38) and improves memory in middle‐aged rats.